Using micro-geography to understand the realisation of wellbeing: A qualitative GIS study of three social enterprises. (March 2020) - Farmer, Jane; Kamstra, Peter; Brennan-Horley, Chris; De Cotta, Tracy; Roy, Michael; Barraket, Jo; Munoz, Sarah-Anne; Kilpatrick, Sue
Abstract: Social enterprises are promoted as a method of welfare reform, to transition people out of disadvantage by addressing poverty, unfulfilled capabilities and social exclusion. This study explores how three Work Integration Social Enterprises (WISEs) in Australia help to realise wellbeing for their employees by mapping their micro-geographical experience of wellbeing. By mapping the sites within a social enterprise where wellbeing is realised, we provide a practical, empirical and replicable methodology that is useful for gaining insights into where and how wellbeing realisation occurs. This situates wellbeing as an upstream place-based resource likely to influence downstream health outcomes. Highlights: Social enterprises are spaces of wellbeing, but wellbeing is unevenly distributed across the sites. Mapping situates wellbeing as an empirical and upstream place-based resource. Micro-geography of wellbeing can aid social enterprises design for wellbeing outcomes. Work supporting wellbeing is not simply allocating people to one job, in one location. Mobility through tasks in relation to personal aptitudes helps wellbeing to realise.